(untitled) (Педагогіка вищої та середньої школи, 2003)
The individually-oriented point of view on organization juvenil relations in the school The article deals with peculiarities of juvenile relations in children. The harmonious decision of contradictions between a person’s aspiration for freedom and his social nature such as the necessity in recognition and the need for intercourse as well as the factors influencing relations in schools collective greatly depends on these peculiarities.